A cultura e a educação amazônica na arte dos brinquedos de miriti - Claudete do Socorro Quaresma da Silva; Nazaré Cristina Carvalho (EccoS – Revista Científica)
This paper is about the miriti toy, a secular craft, typically by Amazon contains in their forms elements representing everyday river. Display interfaces of this intangible heritage and culture of the State of Pará, with the Amazonian culture and education. Emphasizes the miriti toys such as the face of the Amazonian culture that bring in their process of making knowledge and practices that perpetuates itself for generations in the region through oral and observation. The city of Abaetetuba, State of Pará, is the main center of manufacture of this toy. This cultural property has a strong presence since the early days in the largest religious festival in Brazil, the Candle of Our Lady of Nazareth, Bethlehem, capital of Pará. Finally, the artisans who pointed toy miriti with his artistic ability and his unique way build education to teach in the Amazon region.